A chemoproteoinformatics approach demonstrates that aspirin increases sensitivity to MEK inhibition by directly binding to RPS5. Issue 2 (16th May 2022) - Watanabe, Motoki; Boku, Shogen; Kobayashi, Kaito; Kurumida, Yoichi; Sukeno, Mamiko; Masuda, Mitsuharu; Mizushima, Katsura; Kato, Chikage; Iizumi, Yosuke; Hirota, Kiichi; Naito, Yuji; Mutoh, Michihiro; et al.
Abstract: MEK inhibitors are among the most successful molecularly targeted agents used as cancer therapeutics. However, to treat cancer more efficiently, resistance to MEK inhibitor-induced cell death must be overcome. Although previous genetic approaches based on comprehensive gene expression analysis or RNAi libraries led to the discovery of factors involved in intrinsic resistance to MEK inhibitors, a feasible combined treatment with the MEK inhibitor has not yet been developed. Here, we show that a chemoproteoinformatics approach identifies ligands overcoming the resistance to cell death induced by MEK inhibition as well as the target molecule conferring this resistance. First, we used natural products, perillyl alcohol and sesaminol, which induced cell death in combination with the MEK inhibitor trametinib, as chemical probes, and identified ribosomal protein S5 (RPS5) as their common target protein. Consistently, trametinib induced cell death in RPS5-depleted cancer cells via upregulation of the apoptotic proteins BIM and PUMA. Using molecular docking and molecular dynamics (MD) simulations, we then screened FDA- and EMA-approved drugs for RPS5-binding ligands and found that acetylsalicylic acid (ASA, also known as aspirin) directly bound to RPS5, resulting in upregulation of BIM and PUMA and induction of cell death in combination with trametinib. Our chemoproteoinformatics approach demonstrates that RPS5 confers resistance to MEK inhibitor-induced cell death, and that aspirin could be repurposed to sensitize cells to MEK inhibition by binding to RPS5.